Koncepcja idealnego terminu w świetle Słownika terminologii lekarskiej polskiej z 1881 roku - Jankowiak, Lucyna Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
The paper demonstrates attributes of an ideal term on the grounds of nineteenth century Polish medical terminology (names of disorders) from a Dictionary of Polish Medical Terminology by S. Janikowski, J. Oettinger and A. Kremer (Kraków 1881). In the first part of this dictionary, approximately 20 thousand foreign language entries are gathered (Latin, German, French, English) together with their Polish equivalents – from one to several records. The sequence of Polish terms assigned to the entries is not random: from the most to the less recommended. It means that the best terms (I call them ideal terms) come first in the synonymic line. And they are (totally 940) the subject of analysis in this paper. It results from the analysis that ideal terms are mostly: 1) native (98.4%); 2) of simple structure (comprising two elements at most – 89.3%); 3) syntactical derivatives (55.1%); 4) of non-specified origin; 5) sometimes having many meanings (12.2%); 6) relatively long-lasting, that means they generally last in the scientific terminology (74.9%) and - a little bit more rarely (more than 58%) – they keep their position of the ideal term; 7) compared to other terms in a synonymic line, in terms of the structure - frequently (65.5%) identical, that is comprising the same number of elements; 8) most frequently (41.7%) of common root – compared to other terms (all of them or just some of them) in a synonymic line.